(untitled) (Bangladesh Journal of Agricultural Research, 2015)
In this study two pairs of primers based on mitochondrial cytochrome oxidase subunit 1 (mtCOI) region and 28S ribosomal RNA (rRNA) gene region were used for identifying very tiny and morphologically indistinguishable parasitoid Encarsia formosa (Gahan) which are specific to this insect. The fragment amplified by these primer pairs were 860 and 650 bp in length. Species specificity test showed that all E. formosa specimens were detected with no cross reactions with other aphelinid species, including E. sophia (Girault & Dodd), E. luteola, E. Inaron and E. Nigricephala. Using phylogenetic cladogram by the sequences analysis of both mtCOI and 28S rRNA genes could be detected in E. formosa accurately in all replicates. Cardinium and Wolbachia secondary endosymbiont were also detected in E. Formosa used by PCR amplification as well as sequence analysis of 16S-23S rDNA gene region. The molecular technique developed here would be useful for rapid and precise species identification, determination of the host spectrum and more effective utilization of E. formosa. This research work has been performed from January 2011 to June 2012 at the insect molecular physiology lab in the Republic of Korea. DOI: http://dx.doi.org/10.3329/bjar.v39i4.22532 Bangladesh J. Agril. Res. 39(4): 563-578, December 2014